2015
DOI: 10.1016/j.jqsrt.2014.10.023
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical room-temperature line list for 15NH3

Abstract: A new room temperature line list for 15 NH 3 is presented. This line list comprised of transition frequencies and Einstein coefficients has been generated using the 'spectroscopic' potential energy surface NH3-Y2010 and an ab initio dipole moment surface. The 15 NH 3 line list is based on the same computational procedure used for the line list for 14 NH 3 BYTe reported recently and should be as accurate. Comparisons with experimental frequencies and intensities are presented.The synthetic spectra show excellen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 67 publications
2
29
0
Order By: Relevance
“…These term values were used to compute the TIPS by direct summation. The TIPS calculated here agree with the values given by Yurchenko et al [56] and Yurchenko et al [57], which are reported to 1600 and 2000 K, respectively. The TIPS are converged to 6000 K. Table 2 shows that for the 14 NH 3 isotopologue there is little difference at the temperatures of the TIPS_2011 study.…”
Section: Ammoniasupporting
confidence: 91%
See 1 more Smart Citation
“…These term values were used to compute the TIPS by direct summation. The TIPS calculated here agree with the values given by Yurchenko et al [56] and Yurchenko et al [57], which are reported to 1600 and 2000 K, respectively. The TIPS are converged to 6000 K. Table 2 shows that for the 14 NH 3 isotopologue there is little difference at the temperatures of the TIPS_2011 study.…”
Section: Ammoniasupporting
confidence: 91%
“…The term values for 14 NH 3 are from Yurchenko et al [56] and those for 15 NH 3 are from Yurchenko et al [57]. The term values are complete to 35 332 and 29 851 cm -1 for the 14 NH 3 and 15 NH 3 isotopologues, respectively.…”
Section: Ammoniamentioning
confidence: 99%
“…We included absorption by H 2 O, CH 4 , CO, CO 2 , NH 3 , PH 3 , H 2 S, HCN, K, Na, FeH, TiO, and VO. We used HITEMP 2010 for H 2 O, CO, and CO 2 (Rothman et al 2010); TheoReTS for CH 4 (Rey et al 2018); and ExoMol for NH 3 and PH 3 (Coles et al 2019;Yurchenko 2015;Sousa-Silva et al 2015).…”
Section: The Lmd Generic Gcmmentioning
confidence: 99%
“…Yurchenko et al published two 14 NH 3 linelists [174,176] and one for 15 NH 3 [177], computed using variational nuclear motion procedures outlined below. The initial 14 NH 3 linelist [176] is only valid for applications up to 300 K, while their hot 14 NH 3 linelist [174], which they named BYTe, is more extensive, more accurate, and more useful for higher temperatures; thus, only BYTe will concern us here.…”
Section: Bytementioning
confidence: 99%